Stereoselective Conversion of Dialkyl-2-(2-acetylphenoxy)-3- (triphenylphosphoranylidene)butanedioates to Dialkyl-(Z)-2-(2-Acetylphenoxy)-2-butenedioates - RAMAZANI, ALI; RAHIMIFARD, MAHSHID; SOULDOZI, ALI; AZIZIAN, ABBAS; KARDAN, MAHSA; NOSHIRANZADEH, NADER; SAFARI, ASIEH (Asian Journal of Chemistry, 2010)
Protonation of the highly reactive 1:1 intermediates, produced in the reaction between triphenylphosphine and dialkyl acetylenedicarboxylates, by 1-(2-hydroxyphenyl)-1-ethanone leads to vinyltriphenylphosphonium salts, which undergo Michael addition reaction with conjugate base to produce dialkyl 2-(2-acetylphenoxy)-3-(triphenylphosphoranylidene)-butanedioates. Silica gel powder was found to catalyze stereoselective conversion of dialkyl 2-(2-acetylphenoxy)-3-(triphenylphosphoranylidene) butanedioates to dialkyl-(Z)-2-(2-acetylphenoxy)-2-butenedioates in solvent-free conditions under microwave irradiation at microwave power 0.5 KW in 3 min.